Study of the influence of gate etching and passivation on current dispersion, trapping and reliability in RF 0.15 μm AlGaN/GaN HEMTs. (November 2022) - Chiocchetta, F.; De Santi, C.; Rampazzo, F.; Mukherjee, K.; Grünenpütt, Jan; Sommer, Daniel; Blanck, Hervé; Lambert, Benoit; Gerosa, A.; Meneghesso, G.; Zanoni, E.; Meneghini, M.
Abstract: In this paper we examine the effect of passivation and gate etching processes on the current dispersion and reliability of AlGaN/GaN HEMTs for RF applications. We compared the performance of HEMTs with a standard gate etching and passivation processes (reference wafer) with the performances of HEMTs with improved etching process (etching variant wafer) and improved passivation process (passivation variant wafer). In order to study the trapping behavior, we performed dispersion measurements in off-state conditions and drain current transients (DCT) and we found that: 1) The use of improved passivation process determines a decrease of current dispersion, in particular at the knee voltage, where current collapse depends on both threshold voltage and on-resistance variation, 2) The trapping process linked to surface states is influenced by the gate etching and passivation processes; the use of improved passivation slows down the trapping/de-trapping kinetics, resulting in a lower impact on dynamic performance. The study of reliability is based on high-temperature reverse bias (HTRB) stresses. The gate-drain diodes are biased in the same voltage stress conditions (VGS, Stress  = -7 V, VDS, Stress  = 50 V) at high temperatures (175 °C) for 24 h. We demonstrated that the improved passivation limits the increase of gate leakage current during HTRB stress and prevents the belly shape effect linked to the presence of donor traps in the surface between SiN and GaN cap. We performed gate step stress increasing the negative voltage applied to the Schottky contact. The electroluminescence images performed during the stress show spots along the gate finger that are the responsible of the failure of the devices. The results presented in the paper provide information on the optimization of GaN HEMTs for RF applications. Highlights: Study of the effect of different passivation processes and gate etching processes on the performance s of AlGaN/GaN HEMTs for RF applications. The use of LPCVD passivation process determines a decrease of current dispersion. LPCVD passivation process and CHF3 plasma etching improve the stability of the threshold voltage under stress. The trapping process linked to surface states is influenced by the gate etching and passivation processes LPCVD passivation increases stability of diode I-V curve during high temperature reverse bias stress tests.